Texture effects and rate-dependent behaviors of notched magnesium bars. (November 2021) - Ravaji, Babak; Datta, Showren; Foster, Caleb; Lloyd, Jeffrey T.; Wilkerson, Justin W.; Joshi, Shailendra P.
Abstract: It is known that the mechanical behavior of many hexagonal close-packed (HCP) materials is sensitive to textural variations. In the technologically important magnesium (Mg) alloys, the anisotropic plastic behaviors and their dependence on different processing-induced textures have been reasonably well studied under relatively simple stress states. However, a detailed assessment of the rate-dependent microstructure–property linkages under triaxial stress states is relatively less explored. In this work, we present a computational investigation of the role played by strain rate, texture, and stress state in the macro–micro mechanical characteristics of Mg alloys. Three-dimensional boundary value problems using smooth and notched round bar geometries subjected to tensile deformation are modeled using a crystal plasticity framework that includes slip and twinning deformation mechanisms. We examine the responses over six orders of magnitudes of strain rates, for three different initial textures that span a broad spectrum of textural strengths, and three specimen geometries that induce varying levels of stress triaxiality. The simulations reveal a remarkable transition of the tensile response from a conventional power-law type to a sigmoidal type for certain combinations of textures, stress triaxiality levels, and strain rates. While the stress response is strongly rate-dependent, the macroscopic deformation anisotropy has a negligible effect from strain rate compared to the role of the stress state and texture. We discuss the potential implications of these observations on the rate-dependent failure of Mg alloys. Highlights: Presents a fully resolved, three-dimensional computational investigation of texture and strain rate effects in Mg alloys. Investigates stress triaxiality coupling effects with rate and microstructure on the macroscopic responses. Assesses potential implications on the material damage tolerance.